LEARNER-MADE VIDEO PROJECT: PRODUCING PRODUCTIVE EFL LEARNERS - Maria Puspa Sari; Ratu Wardarita (Universitas Brawijaya, 2018)
Video project has potential as a media in language learning which can encourage learners to be more confident and independent to speak fluently. This research was conducted to figure out if video project could increase learners’ speaking ability. Prior to the treatment, this one group pretest-posttest experimental study randomly selected one group of learners consisting 26 participants. The results revealed that video project had significant influence on the participants’ speaking. Participants were found more fluent and communicative in their videos.